Lift Enhancement on Unconventional Airfoils - Yeung, W. W. H. (2006)
Lift augmentation on airfoils is a critical task to an aerodynamicist when asked to design new wings. Flow visualization studies on a corrugated airfoil confirm that the trapped vortices lead to a modification of the effective wing shape and an increase in lift. Considerable lift enhancement is found in the experimental measurements on a wing model incorporated with a backward-facing step on the upper surface because of a trapped vortex. Furthermore, a leading-edge rotating cylinder (which behaves like a vortex) effectively extend the lift curve of an airfoil without substantially affecting its slope, thus increasing the maximum lift and delaying stall. While theoretical studies of vortex trapping are limited to airfoils with smooth surfaces, this paper explores the ability of trapping single and multiple vortices on airfoils with surface discontinuities, such as cavities, corrugations, or a rotating cylinder. Streamlines, surface pressure distributions and the vortex trajectories are presented in the hope to advance the knowledge on lift enhancement for flow past unconventional airfoils.